COMPETENCY, ORGANIZATIONAL HYGIENE FACTOR, CAREER SCAFFOLD, EMPLOYEESâ€™ JOB PERFORMANCE AND EMPLOYEESâ€™ TURNOVER INTENTIONSâ€ (Study: The Seminyak Beach Resort & Spa) - I Made Hadi Purnantara (Institut Pariwisata dan Bisnis Internasional, 2018)
This research objective is investigate the influences among competency, organizational hygiene factor, career scaffold, employeesâ€™ job performance and employeesâ€™ turnover intentions in The Seminyak Beach Resort & Spa. A survey was conducted among a sample of 242 employees at the Seminyak Beach Resort & Spa through purposive sampled with bipolar adjective scale questionnaire but only 189 qualified respondent data could be tabulated, those were analyzed using Structural Equation Modeling via AMOS 22.0. According the result of the analysis, competency had positive and significant influence toward employeesâ€™ job performance (Î» = 0,228, CR = 2,759, Ï =0,006) but it had negative influence toward career scaffold (Î» = -0,141, CR = -2,123, Ï =0,034). Otherwise, organizational hygiene factor able to give positive influence toward career scaffold (Î» = 0,840, CR =8,705, Ï =***) and employeesâ€™ job performance (Î» = 0,206, CR =1,133, Ï = 0,257) but it had negative influence on employeesâ€™ turnover intentions (Î» = -0,162, CR = -0,914, Ï =0,361). Also career scaffold as intervening variable able to give positive and significant influence for both employeesâ€™ job performance (Î» = 0,555, CR =2,919, Ï =0,004) and employeesâ€™ turnover intentions (Î» = 0,605, CR =2,938, Ï =0,003). In the meantime, employeesâ€™ job performance had positive and significant influence toward employeesâ€™ turnover intentions (Î» = 0,492, CR =3,516, Ï =***). The Research limitations/implications â€“ Limitations in this research showed other outside factor still giving influence and it might be able to add more variables for next research. Practical implications â€“ The findings provide for a better understanding of how organizational hygiene factor can control employeesâ€™ turnover intention and it as a trigger to boost employeesâ€™ job performance through career scaffold.Â Keyword: Competency, Organizational Hygiene Factor, Career Scaffold, Employeesâ€™ Job Performance And Employeesâ€™ Turnover Intentions